2018
DOI: 10.1080/02813432.2018.1426141
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer patients’ preferences for type of caregiver during survivorship care

Abstract: PurposeColorectal cancer (CRC) survivors are currently included in a secondary care-led survivorship care programme. Efforts are underway to transfer this survivorship care to primary care, but met with some reluctance by patients and caregivers. This study assesses (1) what caregiver patients prefer to contact for symptoms during survivorship care, (2) what patient factors are associated with a preferred caregiver, and (3) whether the type of symptom is associated with a preferred caregiver.MethodsA cross-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 13 publications
1
11
0
1
Order By: Relevance
“…In line with previous findings (Wieldraaijer et al, , ), patients in general reported to be content with their GP. Even before the introduction of the “time out consultation”, two‐thirds of all CRC patients were in contact with their GP between diagnosis and start of treatment.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In line with previous findings (Wieldraaijer et al, , ), patients in general reported to be content with their GP. Even before the introduction of the “time out consultation”, two‐thirds of all CRC patients were in contact with their GP between diagnosis and start of treatment.…”
Section: Discussionsupporting
confidence: 91%
“…Men were significantly more satisfied with their GP's care after the introduction of the consultation. This observation was made in an earlier study (Wieldraaijer et al, 2018), and part of the explanation may be offered by Christen et al (2016), who report that women prefer cancer survivorship care to be organised in a hospital setting over a primary care setting, and speculate this may be because women expect more supportive care in a secondary care setting.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Lastly, patients reported that GP-led follow-up improved the continuity of care. Older men and patients with chronic comorbid diseases had a special preference for GP-led follow-up [44,45,53,56,58,60,69]. Nonetheless, follow-up by GPs comes with disadvantages.…”
Section: Patient Views and Preferences Towards Setting And Manner Of mentioning
confidence: 99%
“…Twelve studies (8%) focused on preferences for certain healthcare services, and specifically (1) preferred care processes (10/12),45 135–143 such as continuity of care, accessibility and acceptance of the substitution of a physician by nurses and (2) service models (2/12),31 144 perhaps asking patients about their preferences regarding Chronic Care Model recommendations 31…”
Section: Resultsmentioning
confidence: 99%